Following Up on Employee Surveys: A Conceptual Framework and Systematic Review - Huebner, Lena-Alyeska; Zacher, Hannes (Frontiers in Psychology, 2021)
Employee surveys are often used to support organizational development (OD), and particularly the follow-up process after surveys, including action planning, is important. Nevertheless, this process is oftentimes neglected in practice, and research on it is limited as well. In this article, we first define the employee survey follow-up process and differentiate it from other common feedback practices. Second, we develop a comprehensive conceptual framework that integrates the relevant variables of this process. Third, we describe the methods and results of a systematic review that synthesizes the literature on the follow-up process based on the conceptual framework with the purpose of discussing remaining research gaps. Overall, this paper contributes to a better understanding of the organizational and human factors that affect this process. This is useful for practitioners, as it provides guidance for the successful implementation of this human resource practice. For example, research suggests that it is important to enable managers as change agents and to provide them with sufficient resources.